Back to furtado via kaldor and thirlwall: Heterodox theories of growth as a support for the resumption of the furtadian focus of the regional issue - de Lourenço, André Luís Cabral; Bezerra, Márcia Maria de Oliveira; da Silva, Marconi Gomes; Pereira, William Eufrasio Nunes (Revista Econômica do Nordeste, 2016)
This paper aims to present and compare the heterodox growth theories for open economies of Thirlwall and Kaldor to assess how they can contribute as an element of interpretation of the Brazilian heterodox regional economic literature. The hypothesis of the paper is that the lack of autonomy to formalize the internal borders between regions of a country does not constitute an obstacle for the trade effects between them to generate situations characterized by balanceof-payments-constraints, imposing limits to the expansion of their economies and in these processes unleashing polarization mechanisms regarding their growth rates. It is concluded that the literature below justifies the reestablishment of Furtado’s perspective as a key to the interpretation and treatment of regional problems in Brazil.